Prevalence of sexual activity and associated factors in hypertensive males and females in China: A cross-sectional study - Chen Xiaojun; Zhang Qingying; Tan Xuerui (BMC, 2012)
Abstract Background Hypertension is an important factor contributing to sexual dysfunction. The number of people with hypertension is increasing in China, but research into sexual life, which has implications for quality of life, is limited. We aimed to compare sexual activity and the influence of daily behaviors and sexual domain of hypertensive males and females in south China. Methods A cross-sectional study was conducted at the health care center of a university-affiliated hospital from 2007 to 2008. We enrolled 502 subjects with hypertension (225 males, 48.79 ± 7.39 years old; 277 females, 48.26 ± 6.93 years old) and 173 with normotension (82 males, 45.69 ± 6.58 years old; 91 females, 46.14 ± 7.03 years old), all sexually active. All subjects completed a self-administered questionnaire on sexual activity before a routine physical check-up. Data were collected on sociodemographic and clinical characteristics, use of cigarettes and intake of beverages (including alcohol). Results Hypertensive and normotensive subjects differed in frequency of orgasms and of sexual satisfaction, as well as duration of sexual activity. For hypertensive men, low frequency of sexual activity, orgasms and satisfaction were associated with unemployed or retired status than physical labor work (odds ratio [OR] 0.28 [95% confidence interval (95% CI) 0.12-0.69], 0.32 [0.12-0.86], 0.33 [0.19-0.88], respectively; p < 0.05), and long sexual duration was associated with never drinking alcohol than heavy drinking (OR 4.49 [1.28-6.41]). For hypertensive women, low frequency and duration of sexual activity and low satisfaction were associated with never drinking tea than heavy tea drinking (OR 0.42 [0.18-0.96], 0.49 [0.24-0.98], 0.29 [0.14-0.64], respectively; p < 0.05). Medication use and electrocardiography results were not associated with sexual activity for hypertensive patients. Conclusions For hypertensive people in China, lifestyle factors are associated with sexual dysfunction, which differs by the sex of the person. Further research needs to examine serum hormone levels to validate the result.